2018
DOI: 10.3390/ijms19072037
|View full text |Cite
|
Sign up to set email alerts
|

Farrerol Ameliorates TNBS-Induced Colonic Inflammation by Inhibiting ERK1/2, JNK1/2, and NF-κB Signaling Pathway

Abstract: Farrerol, a type of 2, 3-dihydro-flavonoid, is obtained from Rhododendron. Previous studies have shown that Farrerol performs multiple biological activities, such as anti-inflammatory, antibacterial, and antioxidant activity. In this study, we aim to investigate the effect of Farrerol on colonic inflammation and explore its potential mechanisms. We found that the effect of Farrerol was evaluated via the 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis model in mice and found that Farrerol has a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…These ndings suggest that HBEGF serves as a prophylactic or therapeutic agent for the prevention or treatment of intestinal diseases such as hypo-perfusion injury and peritonitis-induced sepsis. Extracellular signal-regulated kinase (ERK)1/2 MAPK, PI3K/AKT, nucleotide-binding oligomerization domain-containing protein 1/2, c-Jun N-terminal kinase (JNK)1/2, and STAT signaling pathways are involved in intestinal barrier function and wound healing (11,45,49). The present study reported that HBEGF ameliorates LPS-induced intestinal dysfunction via PI3K/AKT and P38 signaling pathways.…”
Section: Discussionmentioning
confidence: 70%
“…These ndings suggest that HBEGF serves as a prophylactic or therapeutic agent for the prevention or treatment of intestinal diseases such as hypo-perfusion injury and peritonitis-induced sepsis. Extracellular signal-regulated kinase (ERK)1/2 MAPK, PI3K/AKT, nucleotide-binding oligomerization domain-containing protein 1/2, c-Jun N-terminal kinase (JNK)1/2, and STAT signaling pathways are involved in intestinal barrier function and wound healing (11,45,49). The present study reported that HBEGF ameliorates LPS-induced intestinal dysfunction via PI3K/AKT and P38 signaling pathways.…”
Section: Discussionmentioning
confidence: 70%
“…These findings suggest that HBEGF serves as a prophylactic or therapeutic agent for preventing or treating intestinal disorders, such as hypo-perfusion injury and peritonitis-induced sepsis. The extracellular signal-regulated kinase (ERK)1/2 MAPK, PI3K/AKT, nucleotide-binding oligomerization domain-containing protein 1/2, c-Jun N-terminal kinase (JNK)1/2, and STAT signaling pathways are involved in intestinal barrier function and wound healing [ 11 , 44 , 48 ]. The present study showed that HBEGF alleviated LPS-induced intestinal dysfunction through PI3K/AKT and P38 signaling pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Farrerol directly inhibited the kinase activity of GSK-3β to activate the Nrf2-ARE pathway and further attenuate oxidative stress damage in EA.hy926 cells. 15 Oxidative Medicine and Cellular Longevity…”
Section: Defensive Gene Expressionmentioning
confidence: 99%
“…Farrerol is the major bioactive component isolated from the leaves of traditional Chinese herb Rhododendron dauricum L. As a naturally occurring flavanone, it (Figure 1(a)) has the same core structure as naringenin but contains two additional methyl groups on the ring A. It has been documented that farrerol possesses many biological activities, such as antioxidative, anti-inflammatory, antibacterial, anticancer, and inhibition of VSMC proliferation [14][15][16][17][18]. Recent studies from our group also indicate that farrerol has a positive influence on cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%